Evaluation of Dosimetric Efficacy of RapidArc and Intensity-modulated Radiation Therapy Techniques in Head-and-Neck Cancers - Pratibha Singh; Manoj Kumar Singh; Atul Mishra (Journal of Medical Physics)
Aim: This study aims to compare the dosimetric efficacy of RapidArc (RA) and intensity-modulated radiation therapy (IMRT) in the treatment of head-and-neck cancer, focusing on treatment efficiency and organ at risk (OAR) dose. Materials and Methods: A cohort of 10 patients with head-and-neck cancer was recreated for RA, which was earlier treated with IMRT techniques. Dosimetric parameters evaluated or planning target volume (PTV) included monitor units (MUs), beam on time (BoT), gamma passing rate (GP), and various normal tissue dose indices such as V95, V90, V50, V25, and gradient indices (gradient index [GI], low GI [LGI], high GI). In addition, doses of OARs, including the spinal cord, brainstem, cochleae, esophagus, lips, larynx, and parotid glands, were compared. Results: RA demonstrated significant improvements in treatment efficiency, requiring fewer MU and shorter BoT, while maintaining comparable GP to IMRT. RA achieved a lower LGI, indicating better sparing of normal tissues from intermediate doses. Most other dosimetric parameters, including those for the spinal cord, parotid glands, and PRV spinal cord, demonstrated significant differences, with the RA technique showing superior performance. Conclusion: This study highlights the dosimetric superiority of RA over IMRT, with significantly fewer MU, reduced BoT, and comparable GPs. RA achieved slightly higher mean PTV doses with similar homogeneity and conformity while delivering lower doses to critical OARs, such as the spinal cord, PRV spinal cord, and parotid glands, making it clinically advantageous.